2006
DOI: 10.1177/1934578x0600100306
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Chemical Composition of the Essential Oil of Lippia oreganoides Collected in Two Different Seasons in Venezuela

Abstract: The essential oils from the leaves of Lippia oreganoides collected in June 2003 (rainy season) and February 2004 (dry season) were analyzed by GC/MS. Thymol (61.9% and 44.7%, respectively) and carvacrol (7.9% and 16.8%, respectively) proved to be the major constituents of both collections. Linalool (0.4%) was present only in the collection made in June 2003, while carvacryl acetate (0.6% and caryophyllene oxide (1.6%) were only detected in the February 2004 collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…65 and 23% of the total GC chromatographic area, respectively. Rojas et al 13 compared the compositions of L. origanoides oils from leaves collected during the rainy and dry seasons in Venezuela. Thymol (45–62%) was the main component in these oils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…65 and 23% of the total GC chromatographic area, respectively. Rojas et al 13 compared the compositions of L. origanoides oils from leaves collected during the rainy and dry seasons in Venezuela. Thymol (45–62%) was the main component in these oils.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Colombian chemotype C described here is similar to that found by Rojas et al . 13 in Venezuela. Two chemotypes, “carvacrol” and “thymol”, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveira et al [7] reported the composition of a L. origanoides essential oil corresponding to a different region (Oriximiná, Pará state, Brazil), in which carvacrol was also the main constituent (38%), followed by thymol (18%) and p-cymene (10%). Rojas et al [9] compared the compositions of L. origanoides oils from leaves collected during the rainy and dry seasons in Venezuela. Thymol (61.9 and 44.7%) and carvacrol (7.9 and 16.8%) were the main components of these oils, respectively.…”
mentioning
confidence: 99%
“…Dos Santos et al (2004), analyzing three collections of L. origanoides also observed carvacrol as the main compound (33.5 to 42.9 %). However, in a research comparing the chemical composition of the essential oils of L. origanoides, from the leaves collected in the dry and rainy seasons, thymol was found as the main compound (45 to 62 %) (Rojas et al, 2006). In a study of the chemical composition of the essential oil of L. origanoides in a natural population of plants thymol, was also the main compound (34 a 60 %) (Vicuña et al, 2010).…”
Section: Discussionmentioning
confidence: 98%